Lithium-ion batteries and electronic devices

By leaving space in the packaging film of lithium-ion batteries, adjusting the gap between the battery cell and the packaging film, the deformation and volume expansion of the battery cell during charging and discharging is solved, and the cycle stability and product advantage of the battery are improved.

CN115053376BActive Publication Date: 2024-12-31NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080095314.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-03-11
Publication Date
2024-12-31
Estimated Expiration
2040-03-11

AI Technical Summary

Technical Problem

In lithium-ion batteries, the battery cells are deformed and volume expansion problems during the charging and discharging process due to the winding process, especially the volume expansion of the silicon-containing negative electrode sheet is more serious, affecting the cycle stability of the battery.

Method used

By leaving space in the punching pit of the outer packaging film, adjusting the gap between the battery cell and the packaging film, adjusting the width of the semi-charged full battery according to the volume expansion degree of the negative electrode sheet, ensuring the stability of the battery cell during the charging and discharging process.

Benefits of technology

It effectively alleviates the deformation of the battery cell, improves the cycle stability and product efficiency of the battery, and ensures the performance of the battery during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115053376B_ABST
    Figure CN115053376B_ABST
Patent Text Reader

Abstract

A lithium-ion battery and an electronic device. The battery includes a battery cell, an electrolyte, and a packaging film (2). The battery cell is formed by winding a positive electrode plate and a negative electrode plate separated by a separator. The lithium-ion battery is charged to half to obtain a half-charged full battery. After removing the packaging film (2) from the half-charged full battery, a half-charged battery cell is obtained. When the width of the half-charged full battery is w1, the width of the half-charged battery cell is w2, and g = w2 / w1, the following conditional formula (1) is satisfied: 0.4 < g < 0.997; and, the negative active material of the negative electrode plate includes a silicon-based material. When the capacity per unit volume of the negative electrode plate is a, a and g satisfy the following conditional formula (2): 420 mAh / cm 3 < g×a < 2300 mAh / cm 3 , where 619 mAh / cm 3 < a < 3620 mAh / cm 3 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a lithium ion battery and an electronic device. Background Art

[0002] Soft-package lithium-ion batteries usually include battery cells and packaging films, among which the winding process for battery cells is widely used in the field of lithium-ion batteries due to its high production efficiency. However, the electrode sheets used for winding in the winding process are relatively long (usually greater than 40 cm), and the positive and negative electrode sheets expand in different degrees during the charge and discharge cycle, especially the volume expansion of silicon-containing negative electrode sheets is more serious, so that the wound battery cells have deformation and wrinkles after the formation capacity test. However, since the silicon-containing negative electrode sheet has a higher unit volume capacity, it is the most promising negative electrode sheet for the next generation of lithium-ion batteries. Therefore, it is very important to improve the expansion and deformation problems of lithium-ion batteries, especially lithium-ion batteries with silicon-containing negative electrode sheets. Summary of the invention

[0003] In view of the problem of expansion and deformation of the battery cells in the above-mentioned lithium-ion batteries, the present invention provides a lithium-ion battery and a method for preparing the same, which effectively improves the deformation of the battery cells and improves the cycle stability of the entire battery by reserving space in the punch holes of the outer packaging film (packaging film) to alleviate the expansion.

[0004] To this end, the present invention provides a lithium ion battery, which includes a battery cell, an electrolyte and a packaging film, wherein the battery cell is formed by a positive electrode sheet and a negative electrode sheet separated by a separator and wound, and the lithium ion battery is half-charged to obtain a half-charged full battery, and the packaging film is removed from the half-charged full battery to obtain a half-charged cell,

[0005] When the width of the half-charged battery is w1, the width of the half-charged cell is w2, and g = w2 / w1 When , the following condition (1) is satisfied:

[0006] 0.4<g<0.997 (1);

[0007] Furthermore, the negative electrode plate comprises a silicon-based material. When the capacity per unit volume of the negative electrode plate is a, a and g satisfy the following conditional formula (2):

[0008] 420mAh / cm 3 < g ×a<2300mAh / cm 3 (2)

[0009] Among them, 619mAh / cm 3 <a<3620mAh / cm 3 .

[0010] Specifically, the width w1 of the half-charged full battery refers to the minimum width of the half-charged full battery (including packaging film and battery cell) obtained after the lithium-ion battery is half-charged, usually measured with a vernier caliper; the width W2 of the half-charged battery refers to the maximum distance between the left corner and the right corner of the outermost circle of the battery cell after the packaging film is removed from the half-charged full battery, usually measured with a vernier caliper. When the number of winding layers and the width of the battery cell are constant, the gap between the battery cell and the punching hole of the packaging film is adjusted according to the volume expansion degree of the negative electrode plate, and then the width of the half-charged full battery is adjusted, which can effectively alleviate the volume expansion and improve the deformation of the battery cell, improve the cycle stability of the full battery, and improve the product quality rate.

[0011] In the lithium-ion battery of the present invention, the silicon-based material preferably includes at least one of nano-silicon, silicon oxide, silicon-carbon composite material or silicon alloy material.

[0012] In the lithium-ion battery of the present invention, the silicon-based material is preferably in a granular form, and its average particle size is preferably 500 nm to 30 μm.

[0013] In the lithium-ion battery of the present invention, the nano-silicon is preferably in a granular form, and its average particle size is preferably less than 100 nm.

[0014] The lithium-ion battery of the present invention, wherein the silicon oxide is preferably SiO X , where 0.6≤x≤2.

[0015] In the lithium-ion battery of the present invention, the positive electrode active material of the positive electrode plate is preferably selected from at least one of the group consisting of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel oxide, lithium nickel cobalt oxide and lithium nickel cobalt manganese oxide.

[0016] In the lithium-ion battery of the present invention, the separator is preferably selected from at least one of the group consisting of polyethylene, polypropylene and polyvinylidene fluoride.

[0017] In the lithium-ion battery of the present invention, the packaging film is preferably an aluminum-plastic film.

[0018] In the lithium-ion battery of the present invention, the packaging film preferably has a thickness of 67 to 153 μm and a tensile strength of 4 to 10 N / mm.

[0019] The present invention also provides a method for preparing a lithium ion battery, comprising the following steps:

[0020] S1. Mixing the positive electrode active material with the conductive agent, the binder and the solvent to form a mixed slurry, coating the mixed slurry on the substrate, and obtaining the positive electrode sheet after drying, cold pressing and slitting;

[0021] S2, mixing the negative electrode active material with the conductive agent, the binder and the solvent to form a mixed slurry, coating the mixed slurry on the substrate, and obtaining the negative electrode sheet after drying, cold pressing and slitting;

[0022] S3, stacking the positive electrode sheet, the separator, and the negative electrode sheet in order, and then winding them to obtain a battery cell; and

[0023] S4, put the battery cell into the packaging film, inject the electrolyte after drying and seal it, and obtain the full battery after formation, degassing and trimming.

[0024] After the full battery is half-charged, a half-charged full battery is obtained. After the packaging film is removed from the half-charged full battery, a half-charged cell is obtained. When the width of the half-charged full battery is w1, the width of the half-charged cell is w2, and g=w2 / w1, the following conditional formula (1) is satisfied:

[0025] 0.4<g<0.997 (1);

[0026] Furthermore, the negative electrode active material of the negative electrode plate comprises a silicon-based material. When the capacity per unit volume of the negative electrode plate is a, a and g satisfy the following conditional formula (2):

[0027] 420mAh / cm 3 <g×a<2300mAh / cm 3 (2)

[0028] Among them, 619mAh / cm 3 <a<3620mAh / cm 3 .

[0029] The present invention also provides an electronic device, which includes: the above-mentioned lithium-ion battery.

[0030] The lithium-ion battery and preparation method thereof provided by the present invention adjust the gap between the battery cell and the punching hole of the packaging film according to the volume expansion degree of the negative electrode plate, and then adjust the width of the half-charged full battery, which can effectively alleviate the volume expansion and thus improve the deformation of the battery cell, improve the cycle stability of the full battery, and increase the quality rate of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the cross-sectional structure of a half-charged full battery of the present invention;

[0032] Figure 2 The battery cell of Example 6 after 100 cycles (the Ripple value of the battery corresponding to the measured battery cell is 0.8%);

[0033] Figure 3This is the battery cell of Comparative Example 4 after 100 cycles (the Ripple value of the battery corresponding to the measured battery cell is 7.2%);

[0034] Figure 4 This is the battery cell of Comparative Example 1 after 100 cycles (the Ripple value of the battery corresponding to the measured battery cell is 5.8%).

[0035] Reference numerals:

[0036] 1. Punching holes; 2. Packaging film; 3. Gap;

[0037] w1, width of a half-charged battery; w2, width of a half-charged cell. DETAILED DESCRIPTION

[0038] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.

[0039] I. Definition of terms

[0040] 1. Wrinkles and deformation

[0041] In the present invention, wrinkles refer to the phenomenon of continuous bending of the isolation membrane and the positive / negative electrode sheets; deformation refers to: deformation occurs when Ripple>2%, and Ripple>4% is severe deformation, where Ripple=flat surface thickness of the whole battery (PPG) / point thickness of the whole battery (MMC)-1.

[0042] 2. Half charge

[0043] Definition: A full battery charged to the range of 3.7V to 4.0V is called a half-charged full battery; the process is called half-charging.

[0044] 2. Battery performance test:

[0045] 1. Full battery deformation test:

[0046] PPG is defined as the flat surface thickness of the whole battery. The thickness is measured using a cell flat plate thickness gauge. The whole battery is placed inside a 700g PPG plate, and the surface thickness of the whole battery is measured three times in sequence, and the average of the three data is taken. MMC is defined as the point thickness of the whole battery. Three points are taken at intervals along the vertical direction of the Al tab below the tab, and the thickness is measured with a micrometer and the average value is taken. Ripple is defined as PPG / MMC-1, and the thickness data of the whole battery after 100 cycles is taken as the judgment point. When Ripple>2%, deformation occurs, and Ripple>4% is severe deformation.

[0047] 2. Full battery cycle performance test:

[0048] High temperature cycle test: the test temperature is 45°C, the battery is charged to 4.4V at 0.7C constant current, charged to 0.025C at constant voltage, and discharged to 3.0V at 0.5C after standing for 5 minutes. The capacity obtained in this step is taken as the initial capacity, and a cycle test is performed at 0.7C charge / 0.5C discharge. The capacity at each step is compared with the initial capacity to obtain a capacity decay curve. The present invention illustrates the battery cycle performance by counting the number of cycles at which the capacity decays to 80% of the initial capacity.

[0049] 3. Specific Examples and Comparative Examples

[0050] Example 1

[0051] Preparation of full battery

[0052] (1) The positive electrode active material LiCoO2, conductive carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a weight ratio of 96.7:1.7:1.6, and then coated on an Al foil, dried, cold pressed, and slit to obtain a positive electrode sheet.

[0053] (2) Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 0 to 5 wt %, and the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system in a weight ratio of 95:1.2:3.8, and then coated on a Cu foil, dried, cold pressed, and cut into strips to obtain a negative electrode sheet;

[0054] When the negative electrode active material is coated on the Cu foil, the coating weight is 9.74 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 0-5wt%, so that the capacity a per unit volume of the negative electrode plate is 619.8 mAh / cm 3 .

[0055] (3) Using a polyethylene (PE) porous polymer film as an isolating membrane, the positive electrode sheet, the isolating membrane, and the negative electrode sheet are stacked in order, so that the isolating membrane is placed between the positive and negative electrodes to play an isolating role, and then wound to obtain a battery cell.

[0056] (4) Preparation of electrolyte: In a dry argon environment, lithium hexafluorophosphate (LiPF6) was added to a solvent solution of propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) in a weight ratio of 1:1:1, and the mixture was mixed evenly, wherein the concentration of LiPF6 was about 1.15 mol / L. Then, 12 wt% of fluoroethylene carbonate (FEC) was added and mixed evenly to obtain an electrolyte.

[0057] (4) The battery cell is encapsulated into the punched hole 1 of the packaging film 2 (the aluminum-plastic film comprises an outer layer of nylon, an intermediate layer of Al and an inner layer of PP, and its thickness and strength are shown in Table 1), and after drying, the electrolyte is injected and encapsulated, and a full battery is obtained after formation, degassing and trimming;

[0058] By controlling the gap 3 between the cell and the punch hole, the width of the full battery after half charge is w1 = 15.7 mm, and the width of the cell after half charge is w2 = 15.6 mm. At this time, g = 0.99, g × a = 613.6 mAh / cm 3 .

[0059] in

[0060] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0061] Example 2

[0062] The capacity per unit volume of the negative electrode is also 619.8 mAh / cm 3 The difference from Example 1 is that, during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=36.7 mm, and the width of the battery cell is w2=36.1 mm. At this time, g=0.98, g×a=607.4 mAh / cm 3 .

[0063] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0064] Example 3

[0065] The difference from Example 1 is that

[0066] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO XThe proportion of the negative electrode active material is 10-15wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on a Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0067] When the negative electrode active material is coated on the Cu foil, the coating weight is 7.27 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 10-15wt%, so that the capacity a per unit volume of the negative electrode plate is 957.8mAh / cm 3 .

[0068] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=17.1 mm, and the width of the battery cell is w2=16.5 mm. At this time, g=0.96, g×a=919.5 mAh / cm 3 .

[0069] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0070] Example 4

[0071] The capacity per unit volume of the negative electrode is also 957.8 mAh / cm 3 The difference from Example 3 is that, during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=37.2 mm, and the width of the battery cell is w2=36.2 mm. At this time, g=0.97, g×a=929.1 mAh / cm 3 .

[0072] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0073] Example 5

[0074] The difference from Example 1 is that

[0075] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 20-25wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on a Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0076] When the negative electrode active material is coated on the Cu foil, the coating weight is 5.324 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 20-25wt%, so that the capacity a per unit volume of the negative electrode plate is 1151.3 mAh / cm 3 .

[0077] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=17.0 mm, and the width of the battery cell is w2=16.0 mm. At this time, g=0.94, g×a=1082.2 mAh / cm 3 .

[0078] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0079] Example 6

[0080] The capacity per unit volume of the negative electrode is also 1151.3 mAh / cm 3 The difference from Example 5 is that during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=37.5 mm, and the width of the battery cell is w2=36.3 mm. At this time, g=0.97, g×a=1116.8 mAh / cm 3 .

[0081] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0082] Comparative Example 1

[0083] The difference from Example 1 is that, during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=36.0 mm, and the width of the battery cell is w2=36.0 mm. At this time, g=0.9992, g×a=619.3 mAh / cm 3 .

[0084] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0085] Comparative Example 2

[0086] The difference from Example 3 is that, during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=16.54 mm, and the width of the battery cell is w2=16.5 mm. At this time, g=0.9975, g×a=955.4 mAh / cm3 .

[0087] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0088] Comparative Example 3

[0089] The difference from Example 5 is that, during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=44.5 mm, and the width of the battery cell is w2=15.6 mm. At this time, g=0.35, g×a=403.0 mAh / cm 3 .

[0090] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0091] Example 7

[0092] The difference from Example 1 is that

[0093] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 30-35wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0094] When the negative electrode active material is coated on the Cu foil, the coating weight is 5.324 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected within 30-35wt% to make the capacity a per unit volume of the negative electrode plate 1336.7mAh / cm 3 .

[0095] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=17.9 mm, and the width of the battery cell is w2=15.9 mm. At this time, g=0.89, g×a=1189.6 mAh / cm 3 .

[0096] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0097] Example 8

[0098] The difference from Example 1 is that

[0099] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 45-50wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on a Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0100] When the negative electrode active material is coated on the Cu foil, the coating weight is 4.181 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 45-50wt%, so that the capacity a per unit volume of the negative electrode plate is 1671.8 mAh / cm 3 .

[0101] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=40.7 mm, and the width of the battery cell is w2=36.9 mm. At this time, g=0.91, g×a=1521.3 mAh / cm 3 .

[0102] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0103] Example 9

[0104] The difference from Example 1 is that

[0105] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 55-60wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on a Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0106] When the negative electrode active material is coated on the Cu foil, the coating weight is 3.265 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 55-60wt%, so that the capacity a per unit volume of the negative electrode plate is 2006.6 mAh / cm3 .

[0107] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=21.8 mm, and the width of the battery cell is w2=15.8 mm. At this time, g=0.72, g×a=1444.8 mAh / cm 3 .

[0108] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0109] Example 10

[0110] The difference from Example 1 is that

[0111] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 80-85wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on a Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0112] When the negative electrode active material is coated on the Cu foil, the coating weight is 2.640 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected within 80-85wt% to make the capacity a per unit volume of the negative electrode plate 2422.2mAh / cm 3 .

[0113] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=78.0 mm, and the width of the battery cell is W2=70.0 mm. At this time, g=0.89, g×a=2155.7 mAh / cm 3 .

[0114] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0115] Embodiment 11

[0116] The difference from Example 1 is that

[0117] Commercial silicon oxide SiO X(0.5<x<1.5, DV50=5μm) is mixed with graphite to obtain a negative electrode active material, and the proportion of commercial silicon oxide SiOx in the negative electrode active material is 90~95wt%. Then, the negative electrode active material, conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0118] When the negative electrode active material is coated on the Cu foil, the coating weight is 2.449 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 90-95wt%, so that the capacity a per unit volume of the negative electrode plate is 2677.7 mAh / cm 3 .

[0119] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=45.9 mm, and the width of the battery cell is w2=35.9 mm. At this time, g=0.78, g×a=2088.6 mAh / cm 3 .

[0120] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0121] Example 12

[0122] The difference from Example 1 is that

[0123] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 95-100wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0124] When the negative electrode active material is coated on the Cu foil, the coating weight is 2.337 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 95-100wt%, so that the capacity a per unit volume of the negative electrode plate is 2839.0 mAh / cm 3 .

[0125] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=35.6 mm, and the width of the battery cell is w2=15.6 mm. At this time, g=0.43, g×a=1220.8 mAh / cm 3 .

[0126] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0127] Embodiment 13

[0128] The difference from Example 1 is that

[0129] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 95-100wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0130] When the negative electrode active material is coated on the Cu foil, the coating weight is 2.590 mg / cm 2 , and control the commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 95-100wt%, so that the capacity a per unit volume of the negative electrode plate is 3600mAh / cm 3 .

[0131] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=35.6 mm, and the width of the battery cell is w2=15.0 mm. At this time, g=0.42, g×a=1512.0 mAh / cm 3 .

[0132] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0133] Comparative Example 4

[0134] The difference from Example 10 is that, during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=36.2 mm, and the width of the battery cell is w2=36.2 mm. At this time, g=1, g×a=2422.2 mAh / cm 3 .

[0135] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0136] Comparative Example 5

[0137] The difference from Example 9 is that, during packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=52.5 mm, and the width of the battery cell is w2=18.9 mm. At this time, g=0.36, g×a=722.4 mAh / cm 3 .

[0138] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0139] Comparative Example 6

[0140] The difference from Example 1 is that

[0141] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 11-20wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on a Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0142] When the negative electrode active material is coated on the Cu foil, the coating weight is 7.560 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 11-20wt%, so that the capacity a per unit volume of the negative electrode plate is 619.8 mAh / cm 3 .

[0143] During packaging, the inner width of the punching hole 1 of the packaging film 2 is controlled to be w1=36.35 mm, and the width of the battery cell is w2=36.3 mm. At this time, g=0.43, g×a=266.5 mAh / cm 3 .

[0144] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0145] Comparative Example 7

[0146] The difference from Comparative Example 6 is that

[0147] Commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO X The proportion of the negative electrode active material is 11-20wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on a Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0148] When the negative electrode active material is coated on the Cu foil, the coating weight is 7.130 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 11-20wt%, so that the capacity a per unit volume of the negative electrode plate is 957.8 mAh / cm 3 .

[0149] When encapsulated, g×a=411.9mAh / cm 3 .

[0150] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0151] Comparative Example 8

[0152] The difference from Example 13 is that

[0153] During packaging, the inner width of the punch hole 1 of the packaging film 2 is controlled to be w1=16.46 mm, and the width of the battery cell is w2=16.4 mm. At this time, g=0.996, g×a=3585.6 mAh / cm 3 .

[0154] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0155] Comparative Example 9

[0156] The difference from Example 1 is the thickness and tensile strength of the packaging film 2, see Table 1 for details.

[0157] In addition, commercial silicon oxide SiO X (0.5<x<1.5, DV50=5μm) mixed with graphite to obtain negative electrode active material, commercial silicon oxide SiO XThe proportion of the negative electrode active material is 80-85wt%. Then, the negative electrode active material, the conductive agent acetylene black, and polyacrylic acid (PAA) are fully stirred and mixed in a deionized water solvent system at a weight ratio of 95:1.2:3.8, and then coated on a Cu foil for drying, cold pressing, and striping to obtain a negative electrode sheet.

[0158] When the negative electrode active material is coated on the Cu foil, the coating weight is 2.640 mg / cm 2 , control commercial silicon oxide SiO X The proportion of the negative electrode active material is selected to a certain value within 80-85wt%, so that the capacity a per unit volume of the negative electrode plate is 2422.0 mAh / cm 3 .

[0159] When encapsulated, g×a=2397.8mAh / cm 3 .

[0160] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0161] Comparative Example 10

[0162] The difference from Comparative Example 9 is the thickness and tensile strength of packaging film 2, see Table 1 for details.

[0163] After obtaining the above-mentioned lithium-ion full battery, battery performance tests were carried out, including battery deformation degree test and battery cycle performance test. The test results are shown in Table 1.

[0164] Table 1

[0165]

[0166]

[0167] See Table 1, where the Ripple value is the value after 100 cycles. When Ripple>2%, deformation occurs, and Ripple>4% is severe deformation; the test method of the unit volume capacity a is as follows: the negative electrode plate (single-sided area) obtained in the embodiment is measured with a micrometer to measure the single-sided plate and the corresponding copper foil thickness (t1 and t2, respectively), and dried in a vacuum drying oven at 85°C for 12 hours. Then, it is cut into discs with a diameter of 1.4 cm by a punch in a dry environment. In a glove box, a metal lithium sheet is used as the counter electrode, and a ceglard composite film is selected as the isolation membrane. The electrolyte is added to assemble a button cell. The battery is charged and discharged using the LAND series battery test to test its charge and discharge performance. The capacity obtained is set to C1 (mAh), then the unit volume capacity a = C1*unit area coating weight / (t1-t2).

[0168] First, the comparison between Examples 1-6 and Comparative Examples 1-3 shows that when the unit volume capacity of the negative electrode plates is the same, controlling different g values ​​will produce different degrees of deformation.

[0169] Specifically, from the group comparison between Example 4 and Comparative Example 2, and Example 6 and Comparative Example 3, it is found that under the premise of the same unit volume capacity, an excessively large or small g value has a more significant effect on the deformation of the battery cell and the battery cycle stability.

[0170] Furthermore, by comparing the groups of Examples 1 and 2 with Comparative Example 1, Examples 3 and 4 with Comparative Example 2, and Examples 5 and 6 with Comparative Example 3, it is found that under the condition of the same unit volume capacity of the negative electrode plate, when the g value is greater than 0.997 or the g value is less than 0.4, the battery cell is severely deformed. When the g value is greater than 0.997, it means that the gap between the battery cell and the pit is small, which is not enough to alleviate the volume expansion of the battery cell. As shown in Comparative Examples 1-2, the battery cell is severely deformed. When g is less than 0.4, as in Comparative Example 3, it means that the gap between the battery cell and the pit is large. On the one hand, when the amount of electrolyte is constant, the space of the battery cell infiltrated is reduced, the solid electrolyte interface (SEI) deteriorates, and the cycle performance deteriorates; on the other hand, the activity of the battery cell in the pit becomes larger, affecting the safety of the battery cell. In addition, the battery cycle performance of severely deformed batteries is also significantly deteriorated. This is because the severe deformation of the battery cell causes voids to form between the electrode and the separator, microcracks to form on the electrode plates, and the solid electrolyte interface (SEI) film to rupture and reorganize, consuming the electrolyte and thus deteriorating the battery's cycle performance.

[0171] Second, by comparing Example 12 with Comparative Examples 6 and 7, it is found that when the g value is the same, the unit volume capacity a of the negative electrode plate is different, and the deformation of the battery cell and the battery cycle stability are also very different. Therefore, for different unit volume capacities a of the negative electrode plates, different g values ​​need to be matched to alleviate volume expansion to further optimize the deformation of the battery cell and the battery cycle stability. In addition, it can be seen from Comparative Examples 6 and 7 that the g value is in the range of 0.4<g<0.997, but g×a is less than 420mAh / cm 3 , the battery cell was severely deformed; similarly, when the g value was in the range of 0.4<g<0.997, but g×a was greater than 2300mAh / cm 3 When the battery cell is placed in the same position, the battery cell is severely deformed, as shown in Comparative Example 8. That is, the volume expansion degree caused by different unit volume capacities a of the negative electrode plate is also different, so different gaps (i.e., the gap between the battery cell and the punching hole of the packaging film) need to be set according to different unit volume capacities a to alleviate the volume expansion to the greatest extent and achieve optimal use of space.

[0172] In summary, g value is a major factor affecting the deformation of the battery cell after cycling. At the same time, different negative electrode unit volume capacity a needs to match different g values ​​to optimize the structure of the battery cell. 3 <a<3620mAh / cm 3 When the g value is between 0.4 < g < 0.997, and g × a is between 420 mAh / cm 3 <g×a<2300mAh / cm 3 Within this range, the deformation of the battery cell and the cycle stability of the battery are greatly improved and enhanced. This shows that starting from the optimization of the battery cell structure, reserving corresponding space according to different unit volume capacities a can effectively alleviate volume expansion, thereby improving the deformation of the battery cell and improving the cycle stability of the battery, thereby improving the product quality rate.

[0173] In addition, referring to Table 1, it can be seen from Comparative Examples 9-10 that the thickness and strength of the aluminum-plastic film have a certain influence on the deformation of the battery cell and the later cycle of the battery. If the aluminum-plastic film is too thin, the tensile strength is insufficient, so that the battery cell will undergo a certain deformation after the cycle; and if the aluminum-plastic film is too thick, although the battery cell does not undergo obvious deformation and the battery cycle performance does not decay, if the volumetric capacity of the whole battery is considered, since the volume of the aluminum-plastic film also participates in the composition of the total volume, the volumetric capacity of the whole battery will be reduced to a certain extent.

[0174] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the present invention.

Claims

1. A lithium-ion battery, comprising a battery cell, an electrolyte and a packaging film, wherein the battery cell is formed by winding a positive electrode sheet and a negative electrode sheet separated by a separator, and the lithium-ion battery is half-charged to obtain a half-charged full battery, and the packaging film is removed from the half-charged full battery to obtain a half-charged battery, characterized in that: When the width of the half-charged battery is w1, the width of the half-charged cell is w2, and g=w2 / w1, the following condition (1) is satisfied: 0.4<g<0.997 (1); Furthermore, the negative electrode plate comprises a silicon-based material. When the capacity per unit volume of the negative electrode plate is a, a and g satisfy the following conditional formula (2): 420mAh / cm 3 <g×a<2300mAh / cm 3 (2), Among them, 619mAh / cm 3 <a<3620mAh / cm 3 .

2. The lithium-ion battery according to claim 1, characterized in that The silicon-based material includes at least one of nano-silicon, silicon oxide, silicon-carbon composite material or silicon alloy material.

3. The lithium-ion battery according to claim 1, characterized in that The silicon-based material is in granular form, and its average particle size is 500nm-30μm.

4. The lithium-ion battery according to claim 2, characterized in that: The nano silicon is in particle form, and its average particle size is less than 100 nm.

5. The lithium-ion battery according to claim 2, characterized in that: The silicon oxide is SiO X , where 0.6≤x≤2.

6. The lithium-ion battery according to claim 1, characterized in that The positive electrode active material of the positive electrode plate is at least one selected from the group consisting of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel oxide, lithium nickel cobalt oxide and lithium nickel cobalt manganese oxide.

7. The lithium-ion battery according to claim 1, characterized in that: The diaphragm is selected from at least one of the group consisting of polyethylene, polypropylene and polyvinylidene fluoride.

8. The lithium-ion battery according to claim 1, characterized in that The packaging film is an aluminum-plastic film.

9. The lithium-ion battery according to claim 1, characterized in that: The packaging film has a thickness of 67 to 153 μm and a tensile strength of 4 to 10 N / mm.

10. An electronic device, characterized in that: Comprising: the lithium ion battery according to any one of claims 1 to 9.